Early overreaching symptoms in soccer players and impaired glucose homeostasis - Gailiuniene, A.; Novikovas, V. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
The purpose of this study was to compare the difference in heart rate, lactate concentration and glucose tolerance in health soccer players (n=23) and these athletes, who have overreaching or overtraining symptoms (n=7). Effect of physical activities on heart rate, blood lactate concentration and glucose homeostasis in two groups investigated in this study.